Post Procedural Left Pulmonary Artery Stenosis and Aortic Coarctation Following Transcatheter Closure of Ductus Arteriosus in Infants and Associated Outcomes - Sadiq, Abubakar; Akhtar, Khurram; Saeed, Maimoona; Rafique, Saima; Imtiaz, Sana (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of Left Pulmonary Artery (LPA) stenosis and aortic coarctation following transcatheter closure of ductus arteriosus and to assess the post-procedural outcomes. Study Design: Quasi- Experimental study. Place and Duration of Study: Armed Forces Institute of Cardiology/ National Institute of Heart Diseases, Rawalpindi, Aug 2023 to Jan 2024. Methodology: Forty Seven patients of both gender who underwent Patent Ductus Arteriosus (PDA) closure and weight having < 10kg were included.All patients were admitted one day prior to the procedure, base line laboratory tests including complete blood count, C-reactive protein, chest x-ray, echocardiography and ECG were performed.Patients were kept in post cath ward/HDU for observations and monitoring for any complications. Patients were called up on day 1, day 7, 1st month, 3rd month and 6th month for follow-up. Results: Out of 47 patients, 18(38.3%) were males and 29(61.1%) were females with mean age 7.67±3.77 months. After PDA closure, 12(25.5%) patients developed coarctation across descending aorta, 3(6.3%) patients developed LPA stenosis which improved with time and none patient had significant coarctation or LPA stenosis at 6 month follow up. PDA type, size, device type and weight of participants were significantly associated with coarctation of aorta and LPA stenosis (p<0.05). Conclusion: Transcatheter PDA device closure is an effective and safe treatment in small infants, although there is small risk of aortic coarctation, left pulmonary artery stenosis and Left ventricular dysfunction that resolved in majority of patient without any further intervention over time.